DIMENSIONAL ACCURACY OF ACRYLIC RESIN DENTURE BASES; HIGH STRENGTH HEAT CURED VERSUS MICROWAVE PROCESSED ACRYLIC RESIN– AN IN VITRO STUDY. (CAHIERS MAGELLANES-NS, 2024)
Aims and objective: Poly-methyl-metacrylate resin has been used commonly for denture bases. Polymerisation shrinkage and release of thermal stresses are the major disadvantages exhibited of these materials. The present study was conducted to evaluate and compare Dimensional accuracy of acrylic resin denture bases;high strength heat cured versus microwave processed acrylic resinMethodology: 30 maxillary acrylic bases (2 mm thick) were made on cast model. These specimens were divided into 3 groups.Group 1: control, high strength heat cure PMMA cured by water bath method (short cycle ) Group2; high strength heat cure PMMA samples cured by water bath method (Long cycle) Group 3; microwave acrylic resin samples cured by microwave energy (550 Wfor 6 min). The base/ cast sets were sectioned transversally in the posterior palatal seal zone. The measurements were made at the right marginal limit, left marginal limit, right ridge crest, left ridge crest and the palatal midline. The existence of gaps between the casts and acrylic was assessed using a stereomicroscope Results: There was no significant difference between high strength heat cure PMMA samples cured by water bath method (Long cycle) and microwave acrylic resin samples cured by microwave energy.Conclusion: The greatest discrepancy were seen in high strength heat cure PMMA samples cured by water bath (short cycle) and lowest discrepancy was seen with the microwaveable acrylic resin samples cured by microwave energy (550 Wfor 6 min)